UJI KUALITAS BUBUK CABAI RAWIT (Capsicum frutescens) BERDASARKAN BERAT TUMPUKAN DAN LAMA PENGERINGAN MENGGUNAKAN CABINET DRYER - Maryam Jamilah; Kadirman Kadirman; Ratnawaty Fadilah (Jurnal Pendidikan Teknologi Pertanian, 2019)
This study aims to determine the effect of stack weight and drying time on the quality of cayenne pepper (Capsicum frutescens) powder. This study used a completely randomized design (CDR) factorial with treatment of stack weight (1 kg, 2 kg and 3 kg) and drying time (14 hours, 18 hours and 22 hours). Test parameters consist of yield, moisture content, and organoleptic test. The data analysis technique of this study uses analysis of variance (ANOVA), if it shows a significant difference followed by Duncan's advanced test of 5%. Based on the results of chemical test research, the treatment of 3 kg stack weight with 14 hours drying time has the highest yield and moisture content. Organoleptic test results for the highest distinctive taste were in the treatment of 2 kg stack weight with 18 hour drying time, while the results of organoleptic test for the highest characteristic odor were in the treatment of 1 kg stack weight with 14 hours drying time.